Single nucleotide variations of the canine RAD51 domains, which directly binds PALB2 and BRCA2 - Ozmen, Ozge; Kul, Selim; Risvanli, Ali; Ozalp, Gozde; Sabuncu, Ahmet; Kul, Oguz (Hokkaido Univ, 2017)
Tumors of the mammary glands are the most common tumors to affect entire female dogs representing between 50-70% of all tumors types, which is three times higher rate of incidence than humans. No other animal species has such high probability of onset of mammary tumors. Homologous recombination (HR) is the most important double-strand breaks (DSBs) repair mechanisms of DNA and RAD51 plays an important role in this repair mechanism. The tumor suppressors RAD51, BRCA2 and PALB2 act together to initiate the chromosomal lesions repair. BRCA2 and PALB2 mutations lead to destabilization of the genome and engender cancer risk. PALB2 binds to DNA and associates with the RAD51 recombinase. In this study we investigate the genetic variations in RAD51 gene, which directly interactions with PALB2 and BRCA2 domains. From a total of 64 canine patients with mammary tumors, 31 mammary tumors with benign and malign carcinomas and the 3 normal mammary glands were used for the study. We have identified 2 SNPs (Single Nucleotide Polymorphisms) and 7 SNVs (Single Nucleotide Variants) in canine RAD51 exon 7- intron 9 regions, among them 7 SNVs and 1 SNPs were detected for the first time in this study.
Keywords: Dog; RAD51; SNPs; Mammary Tumors